Sexual Victimization Among Sorority Women - Hinkel, Amanda (2013)
Numerous studies have shown that sorority women have been found to be at greater risk for sexual victimization (including rape and sexual assault) than non-sorority women (29% to 7% respectively; Minow & Einolf, 2009) for several reasons, including: frequent contact and association with fraternity men, the prevalence of alcohol in Greek life, and the effects alcohol has on the body once it is consumed. This paper summarizes research on the circumstances that increase the likelihood that sorority women will become victims of sexual assault, sexual coercion, or rape. Since the research has suggested that one in four college women are at risk and sorority women are at even greater risk, it is imperative that researchers and college administrators, as well as sorority administrators in this circumstance, know which circumstances lead to sexual victimization of sorority women and how sorority women perceive sexual victimization and their chances for attack so they are better able to prevent it from happening. It is suggested that future research focus on investigating what programs are offered for sorority women to learn how to prevent occurrences of sexual assault and what sorority administrators and advisors do in response to hearing about an incident of sexual victimization among one of their girls